PENGARUH PENAMBAHAN UNSUR MAGNESIUM (MG) TERHADAP KEKERASAN DAN STRUKTUR MIKRO PADA PENGECORAN ALUMINIUM - Cholis, Setiawan Noor (Jurnal Nosel, 2013)
The objective of this research is to investigate the effect of the variations  of the added magnesium  (Mg)  element  on  the  hardness  and  micro  structure  of    aluminum.  Material  for  the research was  aluminum. Prior to further study,  aluminum  was exposed to chemical composition testing to find out its composition definitely.It  consisted  of  several  phases,  namely:  cutting  the  material,  smelting  the  material,  adding  the magnesium  element  at  the  Metal  Laboratory,  Ceper  Polytechnics  of  Manufacture  residing  in Batur, Tegalrejo, Klaten. The micro structure testing and the hardness  testing were conducted at the  Engineering  Material  Laboratory,  Gadjah  Mada  University  residing  at  Jl.  Grafika  No.  2 Yogyakarta. The data of the research were analyzed by using the descriptive analytical methods. The results of the research show that the hardness value of the aluminum increases along with the quantity of the added magnesium element. The increasing amount of magnesium element added into the cast aluminum causes grain size of the aluminum to get smaller.